NPY1 Receptor Agonist Modulates Development of Depressive-Like Behavior and Gene Expression in Hypothalamus in SPS Rodent PTSD Model - Serova, Lidia; Mulhall, Hannah; Sabban, Esther (Frontiers in Neuroscience, 2017)
Delivery of neuropeptide Y (NPY) to the brain by intranasal infusion soon after traumatic stress has shown therapeutic potential, and prevented development of many behavioral and neuroendocrine impairments in the single prolonged stress (SPS) animal model of PTSD. Therefore, we examined whether the Y1R preferring agonist [Leu31Pro34]NPY is sufficient to prevent development of SPS induced depressive-like behavioral changes, and hypothalamic gene expression as obtained with intranasal NPY intervention. Male Sprague-Dawely rats were given intranasal infusion of either NPY (150 µg/rat), a low (68 µg /rat) or high (132 µg/rat) dose of [Leu31Pro34]NPY or vehicle immediately following the last SPS stressor, left undisturbed for one week and then tested for depressive-like behavior together with naïve unstressed controls. Vehicle treated animals had elevated immobility forced swim test (FST) and reduced sucrose preference, which were not observed in animals given NPY or the higher dose of [Leu31Pro34]NPY. This dose of [Leu31Pro34]NPY, like NPY, also prevented the SPS-elicited induction of CRF mRNA in the mediobasal hypothalamus. However, [Leu31Pro34]NPY did not prevent, but rather enhanced, the SPS-triggered induction of GR and FKBP5 mRNA levels in the mediobasal hypothalamus. Thus, [Leu31Pro34]NPY may be as effective as NPY and displays therapeutic potential for preventing development of depressive-like behaviors and dysregulation of the CRF/HPA system in PTSD. However, due to its different effects compared to NPY on GR and FKBP5 a broader agonist, such as NPY, may be more desirable.